Evaluating the Flutter Framework in Academic Education A Study of Student Experience and Challenges in Mobile Application Development - Aisha M. A. Yousef; Laila A. H. Bubaker (African Journal of Advanced Pure and Applied Sciences, 2025)
This paper aims to investigate and consider the Flutter framework and its position in the mobile app development ecosystem, while observing the influences behind its presence and acceptance in this domain. Research methodology was employed consisting of collecting quantitative and qualitative data through the distribution of questionnaires to 100 students in three semesters and analyzing graduation projects developed through the framework. The analysis of Flutter was considered from multiple perspectives, including ease of learning, productivity, responsiveness, and performance. This presented some benefits of use such as compatibility with all major operating systems and an ability to design advanced UIs along with detractors being file size and some issues with accessing native elements of the system. The results showed that flutter provides an efficient and easy to use development environment, making it an attractive option for both beginners and professionals. All things considered; the research highlighted the importance of considering the technical barriers to Flutter to yield the best possible benefit. Based on the above findings, the study recommended the inclusion of Flutter training into any academic app development curriculum, with a focus on informing students about how to overcome the associated technical barriers to improve their future readiness in the job market.